2018
DOI: 10.5194/angeo-2018-24
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ionospheric and thermospheric response to the 27–28 February 2014 geomagnetic storm

Abstract: Abstract. The present work explores the ionospheric and thermospheric responses to the 27–28 February 2014 geomagnetic storm. For the first time, a geomagnetic storm is explored in north Africa using interferometer, all-sky imager and GPS data. This storm was caused by coronal mass ejection (CME) associated flares that occurred on 25 February 2014. A Fabry-Perot interferometer located at the Oukaimeden Observatory (31.206° N, 7.866° W, 22.84° N magnetic) in Morocco provides measurements of the thermospheric ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…A G2 class geomagnetic storm that occurred during 27 February-1 March 2014, due to the arrival at the Earth of the shock of a coronal mass ejection (CME) associated with the solar flare event on 25 February 2014 (Malki et al, 2018). Its main phase is during 17:00-23:00 UT, 27 February, and the minimum Dst index reached −97 nT at 23:00 UT, 27 February.…”
Section: Training Set and Validation Set Results Analysismentioning
confidence: 99%
“…A G2 class geomagnetic storm that occurred during 27 February-1 March 2014, due to the arrival at the Earth of the shock of a coronal mass ejection (CME) associated with the solar flare event on 25 February 2014 (Malki et al, 2018). Its main phase is during 17:00-23:00 UT, 27 February, and the minimum Dst index reached −97 nT at 23:00 UT, 27 February.…”
Section: Training Set and Validation Set Results Analysismentioning
confidence: 99%
“…Thus, fixing TIDI winds based on HWM14 can serve as a fairly straightforward and quick fix until the TIDI zero-wind calibration of the TIDI observations is revised. However, there may be some limitations of using this method because of the known discrepancies between observations and HWM14 (e.g., Malki et al, 2018;Meriwether et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We have seen that the DWM07 significantly underestimates, particularly near midnight, the magnitude of the nighttime zonal disturbance winds. Thermospheric wind measurements over the North African lowlatitude region during the 27-28 February 2014 storm showed that the DWM07 also significantly underestimated the nighttime westward disturbance winds near midnight (Malki et al, 2018). Our simple empirical model provides improved estimates of the storm-driven zonal perturbations for the two geomagnetic storms considered above.…”
Section: 1029/2019ja027256mentioning
confidence: 85%
“…FPI observations from Arequipa showed reductions in the nighttime eastward and poleward winds 24 hr after the onsets of the August 1998 and October 2000 geomagnetic storms (Meriwether et al, 2013). Most recently, Malki et al (2018) reported strong zonal and meridional thermospheric wind perturbations in the westward and equatorward directions around midnight over the northern African sector (31.2°S, 7.8°W, magnetic latitude ~23°N) 6 hr after the onset of the 27-28 February 2014 storm. These results are consistent with predicted delays in the establishment of a steady storm-driven circulation pattern (e.g., Blanc & Richmond, 1980;Richmond & Matsushita, 1975).…”
Section: Introductionmentioning
confidence: 99%